Symmetry mismatch controlled ferroelastic domain ordering and the functional properties of manganite films on cubic miscut substrates. Issue 31 (28th July 2021) - Paudel, Binod; Kang, Kyeong Tae; Sharma, Yogesh; Nakotte, Heinrich; Yarotski, Dmitry; Chen, Aiping
Abstract : This work reports the correlation between functional properties and microstructure in ferroelastic La0.9 Sr0.1 MnO3 epitaxial thin films on SrTiO3 (001) substrates with different miscut angles. Abstract : We have studied the magnetotransport properties and strain release mechanisms in ferroelastic La0.9 Sr0.1 MnO3 (LSMO) epitaxial thin films on SrTiO3 (STO)(001) substrates with different miscut angles. The substrate miscut angle plays a critical role in releasing shear strain and has a huge impact on the properties of the films. The strain relaxes by monoclinic distortion for films on low miscut substrates and for higher miscut substrates, the strain relaxation causes the formation of periodic twin domains with larger periodicities. We observe that the Curie temperature ( T C ) decreases systematically, and magnetoresistance (MR) increases with increasing the miscut angle. Such changes in the magnetic and transport properties could be due to the increased density of phase boundaries (PBs) with the increase of miscut angle. This work provides a way to tailor film microstructures and subsequent functional properties of other complex oxide films on miscut substrates with symmetry mismatch.